Live cell imaging of mechanotransduction - Liu, Bo (The Royal Society, 2010)
Mechanical forces play important roles in the regulation of cellular functions, including polarization, migration and stem cell differentiation. Tremendous advancement in our understanding of mechanotransduction has been achieved with the recent development of imaging technologies and molecular biosensors. In particular, genetically encoded biosensors based on fluorescence resonance energy transfer (FRET) technology have been widely developed and applied in the field of mechanobiology. In this article, we will provide an overview of the recent progress of FRET application in mechanobiology, specifically mechanotransduction. We first introduce fluorescent proteins and FRET technology. We then discuss the mechanotranduction processes in different cells including stem cells, with a special emphasis on the important signalling molecules involved in mechanotransduction. Finally, we discuss methods that can allow the integration of simultaneous FRET imaging and mechanical stimulation to trigger signalling transduction. In summary, FRET technology has provided a powerful tool for the study of mechanotransduction to advance our systematic understanding of the molecular mechanisms by which cells respond to mechanical stimulation.